Advertisement Remove all ads

Advertisement Remove all ads

Advertisement Remove all ads

If `y=sec^-1((sqrtx-1)/(x+sqrtx))+sin_1((x+sqrtx)/(sqrtx-1)), `

(A) x

(B) 1/x

(C) 1

(D) 0

Advertisement Remove all ads

#### Solution

(D)

`Let y=sec^-1((sqrtx-1)/(x+sqrtx))+sin^-1((x+sqrtx)/(sqrtx-1))`

`=cos^-1((x+sqrtx)/(sqrtx-1))+sin^-1((x+sqrtx)/(sqrtx-1)) [because sec^-1(x)=cos^-1(1/x)]`

`therefore y=pi/2`

`dy/dx=d/dx(pi/2)=0`

Concept: The Concept of Derivative - Derivative of Inverse Function

Is there an error in this question or solution?